2014
DOI: 10.1007/s11357-014-9719-z
|View full text |Cite
|
Sign up to set email alerts
|

Mulberry leaf polyphenols delay aging and regulate fat metabolism via the germline signaling pathway in Caenorhabditis elegans

Abstract: Mulberry leaves are an important ingredient in some traditional Chinese medicinal formulas and has been developed for use in functional food products. The antioxidant activity of mulberry leaf extract has been reported to have beneficial effects on diseases in vitro; however, it is not clear which components in mulberry leaf extracts have these functions. Furthermore, the mechanisms of action of these ingredients have not been extensively investigated. In this study, we extracted total mulberry leaf polyphenol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 46 publications
3
23
0
Order By: Relevance
“…It is well known that polyphenolic compounds exhibit wide range of biological activities such as antioxidant, antibacterial, anti-carcinogenic, anti-inflammatory, anti-viral, anti-allergic, estrogenic and immune-stimulating effects (3,(15)(16)(17). Furthermore, several studies also showed that the presence of polyphenolic compounds is very important because these compounds delay aging and regulate fat metabolism in Caenorhabditis elegans, which is used as a model (48) and lower hepatic lipid accumulation (49).…”
Section: Polyphenolic Profile Of Bmltsmentioning
confidence: 99%
“…It is well known that polyphenolic compounds exhibit wide range of biological activities such as antioxidant, antibacterial, anti-carcinogenic, anti-inflammatory, anti-viral, anti-allergic, estrogenic and immune-stimulating effects (3,(15)(16)(17). Furthermore, several studies also showed that the presence of polyphenolic compounds is very important because these compounds delay aging and regulate fat metabolism in Caenorhabditis elegans, which is used as a model (48) and lower hepatic lipid accumulation (49).…”
Section: Polyphenolic Profile Of Bmltsmentioning
confidence: 99%
“…Many natural compounds with antioxidants that have anti-aging activity have been successfully tested in this model (Zheng et al 2014;Sonani et al 2014). This microscopic model system is preferred due to its short life cycle and transparent cuticle, which enables to monitor the physiological changes through a microscope.…”
Section: Introductionmentioning
confidence: 99%
“…The mulberry plant has been reported to be rich in flavonoids that have different biological activities, including its anti-oxidant capacity ( Zheng et al, 2014 ). In this study, MARE treatment of B103 cells was found to stimulate ROS accumulation and further depolarize the MMP.…”
Section: Discussionmentioning
confidence: 99%
“…Another study on leukaemia and melanoma showed that the water extract of mulberry root could disrupt the microtubule assembly of cancer cells; however, it could not arrest cells precisely at the G1 stage as taxol does ( Nam et al, 2002 ). Apart from the anticancer and anti-hyperglycaemic effects, one recent study pointed out that mulberry leaf polyphenols delayed the aging process and regulated fat metabolism in C. elegans ( Zheng et al, 2014 ). Mulberry also plays a protective role against different stresses; for example, it protects pancreatic β-cells from hydrogen peroxide via an anti-oxidant pathway ( Lee et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%